Large Raptor Records in Novosibirsk Region, Russia - Dmitry A. Shtol; Julia O. Kashinskaya (Пернатые хищники и их охрана)
All of the oblast’s raptor are listed in the Red Book of the Novosibirsk Region and are rare and protected, and thus their sightings by bird watchers are of interest to the professional community of ornithologists. We have summarized our sightings in recent years of the eagles, White-Tailed Eagle (Haliaeetus albicilla) and Osprey (Pandion haliaetus) in Novosibirsk Region (Fig. 1), and we present them below.